HTA and Reimbursement Status of Metastatic Hormone‑Sensitive Prostate Cancer, Non-Metastatic Castration-Resistant Prostate Cancer, and Metastatic Castration-Resistant Prostate Cancer Treatments in Europe: A Patient Access Landscape Review - Goran Bencina; Elina Petrova; Demet Sönmez; Sonia Matos Pereira; Ioannis Dimitriadis; Stina Salomonsson (Journal of Health Economics and Outcomes Research)
**Background:** Prostate cancer is the second most common cancer in men, with up to one-third of men being diagnosed in their lifetime. Recently, novel therapies have received regulatory approval with significant improvement in overall survival for metastatic castration-resistant prostate cancer, metastatic hormone-sensitive prostate cancer, and nonmetastatic castration-resistant prostate cancer. To improve decision-making regarding the value of anticancer therapies and support standardized assessment for use by health technology assessment (HTA) agencies, the European Society for Medical Oncology (ESMO) has developed a Magnitude of Clinical Benefit Scale (MCBS).